Design and development of a motor imagery based interfaces of wheelchair in a simulated virtual environment - Jackie, Teh (School of Mechatronic Engineering, 2017)
The scope of this research is confined to the design and development of a Motor Imagery based BCI for power wheelchair's directional control in a virtual environment. Therefore, the discussions in this thesis will be focused on the digital processing procedures for converting Motor Imagery signal into appropriate control signal. Mindset 24 amplifier and a 19 channels EEG cap with unipolar electrode setup will be used for data acquisition. However, the focus for the project will be the location belongs to motor and sensory areas. This is translated into signals emanated from scalp location C3, C4 and Cz based on the 10-20 International System of Electrode Placement.